Jaundice-predominant manifestation of Kawasaki disease in children - Huang, Ya-Ning; Lin, Chien-Yu; Chi, Hsin; Chiu, Nan-Chang; Huang, Daniel Tsung-Ning; Chang, Lung; Kung, Yen-Hsin; Huang, Ching-Ying (Frontiers in Pediatrics, 2024)
A jaundice-predominant presentation of Kawasaki disease (KD) is atypical.A total of 12 children with KD with a predominant manifestation of jaundice at MacKay Children's Hospital were reviewed, along with 42 cases reported in the literature since 1990.The median age of the 12 patients was 1.85 years (range: 3 months to 4 years), and 66.6% were male. All of the patients had elevated liver function at presentation, 50% had hydrops of the gallbladder, and almost 60% had gastrointestinal symptoms and signs. Complete KD was evident in 11 of the 12 patients (91.7%), and 2 patients (16.7%) had recurrent episodes. All of the patients received intravenous immunoglobulin (IVIG); however, one-third were refractory to treatment.Corticosteroids were used in 5 (41.7%) of the patients. Three (25%) of the patients had shock, and 7 (58.3%) had coronary artery abnormalities, of whom 1 (8.3%) had persistent coronary artery aneurysm and the others recovered. A review of the 42 cases in the literature showed that the children with a jaundice-predominant presentation of KD had high rates of IVIG-refractory disease (25%), coronary artery abnormalities (25%), shock (13.2%), and corticosteroid treatment (24.2%).Children with KD presenting with a jaundice-predominant manifestation are at a higher risk of IVIG-refractory disease, coronary artery abnormalities, and more recurrent episodes. Physicians should be aware of the risk of shock in this population.